Factors Associated With Choriocarcinoma Syndrome Development in Poor-Risk Patients With Germ Cell Tumors - Rejlekova, Katarina; Kalavska, Katarina; Makovnik, Marek; Hapakova, Nikola; Chovanec, Michal; De Angelis, Valentina; Obertova, Jana; Palacka, Patrik; Sycova-Mila, Zuzana; Mardiak, Jozef; Mego, Michal (Frontiers in Oncology, 2022)
Background: Germ cell tumors (GCTs) represent a highly curable cancer. However, a small proportion of poor-risk patients can develop choriocarcinoma syndrome (CS) connected with acute respiratory distress syndrome (ARDS) with high mortality rate. Our retrospective study aimed to determine the risk factors of poor-risk GCTs susceptible to CS development. Patients and methods: Using a computerized database and a systematic chart review, we identified the records of 532 patients with GCTs treated at the National Cancer Institute from 2000 to 2018. Ninety eligible patients with poor-risk GCTs based on IGCCCG classification were identified. All patients were treated with platinum-based induction chemotherapy. Clinicopathological variables were collected and analyzed in correlation to CS development. Results: Nine (10%) of 90 patients developed CS in a median of 1 day (1- 9 days) after chemotherapy administration. All patients died shortly after the chemotherapy start with median of 4 days (3-35 days) due to ARDS development. In univariate analysis metastatic lung involvement ≥50% of lung parenchyma, choriocarcinoma elements in histology specimen, dyspnea, cough, hemoptysis, ECOG PS ≥2, weight loss, hemoglobin ≤100 g/l, NLR ≥ 3.3 at the time of presentation were associated with CS development. In multivariate analysis, ECOG PS ≥2 and metastatic lung involvement ≥50% were independently associated with CS. All patients with these two characteristics developed CS, compared to 0% with zero or one of these factors (P < 0.000001). Conclusions: In our study we identified factors associated with CS development. These factors might improve the risk stratification of the patients susceptible to CS and improve their outcome.